CHARACTER IN A WORK OF ART (International conference on multidisciplinary science, 2023)
Character is one of the main tools that serve to express the idea of the work. when creating a creative character, he imposes certain ideological goals on him, therefore, he is the product of long observations and great experience. In this article, various criteria and tasks of character are analyzed through Luqman Borikhon's novel "People in the Heat".